Electrode for water electrolysis, water electrolysis cell, water electrolysis apparatus, and method for manufacturing electrode for water electrolysis
The integration of a layered double hydroxide layer with transition metals and a chelating agent on a conductive base material enhances the performance and durability of water electrolysis electrodes, addressing the inefficiencies in existing technologies and facilitating effective hydrogen production from renewable energy.
Patent Information
- Application Number
- JP2024546740
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-16
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-20
AI Technical Summary
Existing water electrolysis electrodes face challenges in achieving high performance and efficiency, particularly in terms of low overvoltage for both anode and cathode reactions, which are crucial for effectively utilizing surplus renewable energy to produce hydrogen.
A water electrolysis electrode is developed with a sheet-like conductive base material coated with a layered double hydroxide (LDH) layer containing two or more types of transition metals, stabilized by a chelating agent, which is directly bonded to the base material without organic adhesives, enhancing electrode activity and durability.
The electrode exhibits high performance and durability, with reduced overvoltage, enabling efficient hydrogen production from surplus renewable energy, thus improving the utilization of renewable energy sources.
Smart Images

Figure 0007620858000002 
Figure 0007620858000003 
Figure 0007620858000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode for water electrolysis, a water electrolysis cell, a water electrolysis device, and a method for producing an electrode for water electrolysis. [Background technology]
[0002] Electrodes for water electrolysis are conventionally known.
[0003] Patent Document 1 describes a method for producing an electrode for electrolysis of water, which includes a step of immersing an electrode substrate containing a specific layered double hydroxide in an organic solvent. In this method, the electrode substrate is produced by performing an electrodeposition process in an aqueous solution containing a compound containing metal M1 and a compound containing metal M2, using the conductive substrate as the anode.
[0004] Patent Document 2 describes a cathode for electrolyzing an aqueous solution, which comprises a conductive substrate having a nickel surface, a mixed layer, and an electrode catalyst layer. The mixed layer is formed on the surface of the conductive substrate and contains metallic nickel, nickel oxide, and carbon atoms. The electrode catalyst layer is provided on the mixed layer and contains a platinum group metal or a platinum group metal compound.
[0005] Non-Patent Document 1 examines the activity of the oxygen evolution reaction (OER) of an electrode made of Ni-Fe layered double hydride (Ni-Fe LDH).
[0006] Non-Patent Document 2 describes that the interface interaction between FeOOH and Ni-Fe LDH adjusts the local electronic structure of Ni-Fe LDH and enhances the OER electrocatalysis. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2017 / 154134 [Patent Document 2] JP 2011-190534 A [Non-patent literature]
[0008] [Non-Patent Document 1] Seyeong Lee et al., “Operational durability of three-dimensional Ni-Fe layered double hydroxide electrocatalyst for water oxidation,” Electrochimica Acta, 2019, Vol.315, p.94-101 [Non-Patent Document 2] Jiande Chen et al., “Interfacial Interaction between FeOOH and Ni-Fe LDH to Modulate the Local Electronic Structure for Enhanced OER Electrocatalysis,” ACS Catalysis, 2018, Vol.8, p.11342-11351 Summary of the Invention [Problem to be solved by the invention]
[0009] The descriptions in the above documents need to be reconsidered from the viewpoint of improving the performance of electrodes for water electrolysis. Therefore, the present disclosure provides a novel electrode for water electrolysis that is advantageous in terms of exhibiting high performance. [Means for solving the problem]
[0010] The present disclosure relates to A sheet-like conductive substrate; a layered double hydroxide layer containing two or more types of transition metals provided on a surface of the conductive substrate; The layered double hydroxide layer contains a chelating agent. An electrode for water electrolysis is provided. Effect of the Invention
[0011] According to the present disclosure, it is possible to provide a novel water electrolysis electrode that is advantageous in terms of exhibiting high performance. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic diagram of an electrode for water electrolysis according to a first embodiment. [Diagram 2] FIG. 2 is a diagram that illustrates an example of the crystal structure of a layered double hydroxide (LDH). [Diagram 3] FIG. 3 is a diagram illustrating a mechanism for producing the water electrolysis electrode according to the first embodiment. [Figure 4] FIG. 4 is a cross-sectional view illustrating an example of a water electrolysis cell according to the second embodiment. [Diagram 5] FIG. 5 is a cross-sectional view illustrating an example of a water electrolysis apparatus according to a third embodiment. [Figure 6] FIG. 6 is a cross-sectional view illustrating an example of a water electrolysis cell according to a fourth embodiment. [Figure 7] FIG. 7 is a cross-sectional view illustrating an example of a water electrolysis apparatus according to a fifth embodiment. [Figure 8] FIG. 8 is a transmission electron microscope (TEM) image of the electrode according to Example 1. [Figure 9A] FIG. 9A is a TEM image showing a portion of the electrode according to Example 1 for which electron beam diffraction results were obtained. [Figure 9B] FIG. 9B is an electron beam diffraction image obtained by TEM for the portion of the electrode shown in FIG. 9A. [Figure 10] FIG. 10 is a TEM image of the electrode according to the second embodiment. [Figure 11A] FIG. 11A is a TEM image showing a portion of the electrode according to Example 2 for which electron beam diffraction results were obtained. [Figure 11B] FIG. 11B is an electron beam diffraction image obtained by TEM for the portion of the electrode shown in FIG. 11A. [Figure 12] FIG. 12 is a TEM image of the electrode according to Comparative Example 2. [Figure 13A]FIG. 13A is a TEM image showing a portion of the electrode according to Comparative Example 2 for which an electron beam diffraction result was obtained. [Figure 13B] FIG. 13B is an electron beam diffraction image obtained by TEM for the portion of the electrode shown in FIG. 13A. [Figure 14] FIG. 14 is a graph showing the measurement results of the OER overpotential of the electrode according to Example 1. [Figure 15] FIG. 15 is a graph showing the measurement results of the OER overpotential of the electrode according to Example 2. [Figure 16] FIG. 16 is a graph showing the measurement results of the OER overpotential of the electrode according to Example 3. [Figure 17] FIG. 17 is a graph showing the measurement results of the OER overpotential of the electrode according to Example 4. [Figure 18] FIG. 18 is a graph showing the measurement results of the OER overpotential of the electrode according to Example 5. [Figure 19] FIG. 19 is a graph showing the relationship between the OER overpotential and the number of cycles for the electrodes according to Examples 1 and 2 and the electrodes according to Comparative Examples 2 and 3. [Figure 20] FIG. 20 is a Fourier transform infrared spectroscopy (FT-IR) chart of the electrode according to Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] (Findings on which this disclosure is based) As a measure against global warming, the use of renewable energy such as solar and wind power has been attracting attention. However, power generation using renewable energy has the problem of surplus electricity being wasted. For this reason, the efficiency of renewable energy use is not necessarily sufficient. Therefore, a method of making effective use of surplus electricity by producing and storing hydrogen from the surplus electricity is being studied.
[0014] One method for producing hydrogen from surplus electricity is water electrolysis. To produce hydrogen cheaply and stably, there is a need to develop a highly efficient, long-life water electrolysis device.
[0015] In a water electrolysis device, oxygen is generated at the anode, and hydrogen is generated at the cathode. The reaction in which oxygen is generated at the anode is also called an anode reaction, and the reaction in which hydrogen is generated at the cathode is also called a cathode reaction. In order to provide a highly efficient water electrolysis device, it is desirable that the overvoltage is particularly low at the anode. In addition, it is also desirable that the overvoltage is low at the cathode. Thus, there is a demand for the development of high-performance electrodes for the anode reaction or cathode reaction in water electrolysis.
[0016] For example, LDH is considered to be a promising material for electrodes for water electrolysis in terms of its large specific surface area and the variety of combinations of metal ions. According to Patent Document 1, an electrode substrate containing a specific layered double hydroxide is produced by performing an electrodeposition process in an aqueous solution containing a compound containing metal M1 and a compound containing metal M2, using a conductive substrate as the anode. However, it is difficult to say that such a method requiring an electrodeposition process is simple. As a result of extensive investigations, the present inventors have newly discovered that a layer containing LDH and a specific component enhances the performance of a water electrolysis electrode, and have completed the water electrolysis electrode of the present disclosure.
[0017] Hereinafter, the embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments. The embodiments described below are all comprehensive or specific examples. Therefore, the numerical values, shapes, materials, components, arrangement positions and connection forms of the components shown in the following embodiments are examples and are not intended to limit the present disclosure. In addition, among the components in the following embodiments, components that are not described in the independent claims showing the highest concept are described as optional components. In addition, in the drawings, the description of components with the same reference numerals may be omitted. In addition, the drawings are schematic diagrams of each component for ease of understanding, and the shapes and dimensional ratios may not be displayed accurately.
[0018] (First embodiment) FIG. 1 is a cross-sectional view that illustrates a schematic diagram of an electrode for water electrolysis according to a first embodiment. As illustrated in FIG. 1, the electrode for water electrolysis 1 includes a sheet-like conductive substrate 11 and a layered double hydroxide (LDH) layer 12. The LDH layer 12 is provided on the surface of the conductive substrate 11. The LDH layer 12 can function as a catalyst for an anode reaction or a cathode reaction in water electrolysis. The LDH layer 12 is bonded to the conductive substrate 11. The LDH layer 12 is directly bonded to the surface of the conductive substrate 11 without using an adhesive that includes an organic material such as a polymer. The LDH layer 12 includes an LDH that includes two or more transition metals and a chelating agent. In this way, the chelating agent is adjusted to reduce the crystal growth of the LDH during the formation of the LDH layer 12, and the LDH layer 12 that includes the LDH bonded to the surface of the conductive substrate 11 is likely to exist in a desired state. This makes it easier for the electrode activity of the electrode for water electrolysis 1 to be high, and the electrode for water electrolysis 1 can exhibit high performance.
[0019] The conductive substrate 11 is not limited to a specific substrate as long as it has conductivity. The conductive substrate 11 may contain a metal or may contain a resin. The conductive substrate 11 may be entirely made of a metal. The conductive substrate 11 may have a configuration in which a surface layer containing a metal is formed on a member made of a resin such as polypropylene or polyethylene. In this case, the surface layer containing a metal may be a plating film or a sputtering film. The metal contained in the conductive substrate 11 may be a pure metal such as nickel or iron, or an alloy such as stainless steel or Inconel. Inconel is a registered trademark.
[0020] The surface of the conductive substrate 11 is preferably made of nickel. In this case, the conductive substrate 11 is likely to have high alkali resistance. When the surface of the conductive substrate 11 is made of nickel, the entire conductive substrate 11 may be made of nickel, or the conductive substrate 11 may have a surface layer made of nickel. The surface layer made of nickel is a sputtered film or a plated film.
[0021] When the surface of the conductive substrate 11 is made of nickel, the purity of the nickel forming the surface is not limited to a specific value. For example, the purity of the nickel forming the surface of the conductive substrate 11 is 90 mass % or more. This makes it easier for the conductive substrate 11 to have high alkali resistance. The method for determining the purity of the nickel forming the surface of the conductive substrate 11 is not limited to a specific method. The purity of the nickel forming the surface of the conductive substrate 11 may be determined by elemental analysis such as X-ray fluorescence spectrometry (XRF) and energy dispersive X-ray spectrometry (EDX). For example, the purity of nickel may be determined by analyzing an extract obtained by completely dissolving the conductive substrate 11 in aqua regia using a method such as inductively coupled plasma atomic emission spectrometry (ICP-AES). When the purity of nickel is high, the purity of nickel may be determined by comparing the specific gravity of the conductive substrate 11 with the specific gravity of pure nickel.
[0022] The purity of nickel constituting the surface of the conductive base material 11 is desirably 95% by mass or more, more desirably 97% by mass or more, even more desirably 98% by mass or more, and particularly desirably 99% by mass or more.
[0023] The shape of the conductive substrate 11 is not limited to a specific shape as long as it is a sheet. The conductive substrate 11 may have a non-porous structure such as a plate or foil, or may have a porous structure such as an expanded metal, mesh, foam, or nonwoven fabric. The conductive substrate 11 preferably has a porous structure. In this case, the surface area of the conductive portion of the conductive substrate 11 is likely to be large, and the escape of gas generated in the water electrolysis reaction is likely to be prevented.
[0024] The thickness of the conductive substrate 11 is not limited to a specific value. The conductive substrate 11 has a thickness of, for example, 0.02 mm or more. In this case, the conductive substrate 11 tends to be easy to handle. The thickness of the conductive substrate 11 is, for example, 10 mm or less, and preferably 1 mm or less.
[0025] FIG. 2 is a diagram schematically showing an example of the crystal structure of LDH. LDH20 has activity with respect to the gas generation reaction such as hydrogen and oxygen at the anode or cathode of the water electrolysis cell. For example, in alkaline water electrolysis, LDH20 can be changed to a hydroxide by the water electrolysis reaction.
[0026] LDH20 has a composition represented by, for example, the following formula (1). In formula (1), M1 2+ is a divalent transition metal ion. M2 3+ is a trivalent transition metal ion. A n- is an interlayer anion. x is a rational number satisfying the condition 0 < x < 1. y is a number corresponding to the required amount of charge balance. n is an integer. m is an appropriate rational number. [M1 2+ 1-x M2 3+ x (OH)2][yA n- ·mH2O] Formula (1)
[0027] The two or more transition metals in LDH20 are not limited to specific transition metals. In other words, M1 and M2 in the composition shown in formula (1) are not limited to specific transition metals. The two or more transition metals include at least two selected from the group consisting of, for example, V, Cr, Mn, Fe, Co, Ni, Cu, W, and Ru. In this case, the water electrolysis electrode 1 is more likely to have high electrode activity.
[0028] The two or more transition metals in LDH20 preferably include at least one selected from the group consisting of Ni and Fe. In this case, the water electrolysis electrode 1 is more likely to have high electrode activity. In addition, the manufacturing cost of the water electrolysis electrode 1 is likely to be low.
[0029] The two or more transition metals in LDH20 contain Ni and Fe. For example, in the composition shown in formula (1), M1 may be Ni and M2 may be Fe. In this case, the water electrolysis electrode 1 is more likely to have high electrode activity.
[0030] Interlayer anions, A n- may be an inorganic ion or an organic ion. An example of an inorganic ion is CO3 2- , NO3 - , Cl - , SO4 2- , Br - , O.H. - , F - , I - , Si2O5 2- , B4O5(OH)4 2- , and PO4 3- An example of an organic ion is CH3(CH2) n SO 4- , CH3(CH2) n COO - , CH3(CH2) n PO 4- , and CH3(CH2) n NO 3- A n- can be inserted between the layers of the metal hydroxide along with water molecules. n- The charge and ion size of LDH20 are not limited to a specific value. n- may contain multiple types of A n- may also include
[0031] As shown in Figure 2, LDH20 is a 2+ Or M2 3+ At each vertex of the octahedron with - LDH20 has [M1 2+ 1-x M2 3+ x (OH)2] x+ This metal hydroxide has a layered structure in which hydroxide octahedra are connected two-dimensionally by sharing edges. Between the layers of the metal hydroxide, anions A n- and water molecules are present. The metal hydroxide layer acts as a host layer 21, and the anions A n- and a guest layer 22 containing water molecules is disposed between the host layers 21. In other words, the LDH 20 as a whole is composed of a host layer 21 of a metal hydroxide and an anion A n-The LDH 20 has a sheet-like structure in which the guest layer 22 of water molecules and the guest layer 23 of metal hydroxide are alternately laminated. 2+ Part of M2 3+ It has a structure substituted with:
[0032] As described above, the LDH layer 12 contains a chelating agent. The chelating agent may be coordinated to a transition metal ion contained in the LDH 20. This allows the LDH 20 to be stably present in the LDH layer 12. In addition, the LDH 20 is easily synthesized to have a small particle size. In addition, since the LDH 20 nucleated on the surface of the conductive base material 11 is likely to undergo slow crystal growth, the dense LDH layer 12 containing the LDH 20 and having few voids is likely to have a desired thickness relative to the conductive base material 11. This allows the LDH layer 12 to effectively contribute to the anode reaction or the cathode reaction, and the water electrolysis electrode 1 is likely to have high electrode activity.
[0033] The chelating agent is not limited to a specific chelating agent. The chelating agent is, for example, an organic compound capable of coordinating with a transition metal ion in LDH20. The chelating agent may be at least one selected from the group consisting of bidentate organic ligands and tridentate organic ligands. Examples of the chelating agent are β-diketones, β-ketoesters, hydroxycarboxylic acids, and hydroxycarboxylates. Examples of β-diketones are acetylacetone (ACAC), trifluoroacetylacetone, hexafluoroacetylacetone, benzoylacetone, thenoyltrifluoroacetone, dipyrrolylmethane, dibenzoylmethane, and ascorbic acid. Examples of β-ketoesters are methyl acetoacetate, ethyl acetoacetate, allyl acetoacetate, benzyl acetoacetate, n-propyl acetoacetate, iso-propyl acetoacetate, n-butyl acetoacetate, iso-butyl acetoacetate, tert-butyl acetoacetate, 2-methoxyethyl acetoacetate, and methyl 3-oxopentanoate. Examples of hydroxycarboxylic acids and their salts are tartaric acid, citric acid, malic acid, gluconic acid, ferulic acid, lactic acid, glucuronic acid, and their salts.
[0034] The chelating agent preferably contains at least one selected from the group consisting of acetylacetone and citrates. In this case, the water electrolysis electrode 1 is more likely to have high electrode activity. An example of the citrate is trisodium citrate.
[0035] The thickness of the LDH layer 12 is not limited to a specific value. The LDH layer 12 has a thickness of, for example, 35 nm or more. With such a configuration, the water electrolysis electrode 1 is more likely to have high electrode activity. The LDH layer 12 includes a portion having a thickness of, for example, 35 nm or more. The thickness of the LDH layer 12 can be determined, for example, by TEM observation of a cross section of the water electrolysis electrode 1. The thickness of the LDH layer 12 is, for example, 213 nm or less.
[0036] The LDH layer 12 covers, for example, the surface of the conductive base material 11. The coverage of the LDH layer 12 with respect to the surface of the conductive base material 11 is not limited to a specific value. The coverage is preferably 99% or more. In this case, the water electrolysis electrode 1 is more likely to have high electrode activity. In addition, the water electrolysis electrode 1 is more likely to have high durability.
[0037] The method for producing the water electrolysis electrode 1 is not limited to a specific method. The water electrolysis electrode 1 is produced, for example, by immersing the conductive substrate 11 in a solution containing a chelating agent and two or more types of transition metal ions and adjusting the solution to an alkaline state. According to this method, the LDH layer 12 containing LDH and a chelating agent can be formed on the surface of the conductive substrate 11 in a simple manner.
[0038] The temperature of the solution when it is adjusted to be alkaline is not limited to a specific temperature. The temperature of the solution is, for example, room temperature of 20° C.±15° C. In this case, a water electrolysis electrode 1 having high electrode activity is easily obtained.
[0039] The solvent of the solution may be water, an organic solvent, or a mixed solvent of water and an organic solvent.
[0040] The method for producing the water electrolysis electrode 1 preferably includes increasing the pH. This allows the LDH 20 to be formed on the surface of the conductive base material 11 in a short period of time, making it easier to obtain a water electrolysis electrode 1 with high electrode activity. In addition, the produced water electrolysis electrode 1 is likely to have high durability.
[0041] The method of adjusting the solution to be alkaline is not limited to a specific method. For example, the solution may be adjusted to be alkaline by mixing the above solution with an alkaline solution. Alternatively, the solution may be adjusted to be alkaline by adding a pH-raising agent to the above solution. In this case, the pH-raising agent is not limited to a specific compound. The pH-raising agent is, for example, a compound having an epoxy group. Examples of the pH-raising agent are propylene oxide, ethylene oxide, and butylene oxide.
[0042] When a pH-raising agent having an epoxy group such as propylene oxide is added to a solution, the pH-raising agent may capture hydrogen ions present in the solution in the presence of a nucleophile such as chloride ions, accompanying a ring-opening reaction of the epoxy group. This causes the pH of the solution to increase, and the solution may have an alkaline property. The pH of a solution containing a chelating agent and two or more kinds of transition metal ions is, for example, 1. When a pH-raising agent is added to this solution, the pH of the solution may increase gradually from, for example, 1, and the solution may ultimately have an alkaline property. The final pH of the solution may be, for example, 8 or more and 12 or less. The addition of the pH-raising agent to the solution causes a reaction to capture hydrogen ions in the solution. This causes the pH of the solution to increase gradually. The time from the addition of the pH-raising agent to the solution until the pH of the solution reaches a steady state is not limited to a specific time. The time may be, for example, 24 hours or more, and may be several days.
[0043] The two or more types of transition metal ions contained in the solution are not limited to specific transition metal ions. For example, the two or more types of transition metal ions contained in the solution are ions of at least two transition metals selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Cu, W, and Ru. In this case, a water electrolysis electrode 1 having high electrode activity is more easily produced.
[0044] The two or more types of transition metal ions contained in the solution preferably include an ion of at least one transition metal selected from the group consisting of Ni and Fe. In this case, a water electrolysis electrode 1 having high electrode activity can be more easily produced.
[0045] As described above, the surface of the conductive base material 11 is preferably made of nickel. In this case, for example, a water electrolysis electrode having advantageous properties from the viewpoint of achieving both corrosion resistance and electrical conductivity in alkaline water electrolysis can be easily produced.
[0046] The conductive substrate 11 preferably contains nickel. The two or more kinds of transition metal ions contained in the solution preferably contain Fe ions. The solution preferably contains chloride ions. In this case, a reaction shown in formula (2) may occur. As a result, the conductive substrate 11 may be etched. The method for producing the electrode 1 for water electrolysis preferably includes promoting mixing of the solution before adjusting the solution to be alkaline while the conductive substrate 11 is immersed. The promotion of mixing of the solution may be achieved, for example, by vibrating the conductive substrate 11, shaking a container containing the solution and the conductive substrate 11, or stirring the solution using a stirrer piece and a stirrer. According to such a method, forced convection of the solution occurs, and the mixing of the solution may be promoted. As a result, the conductive substrate 11 is etched in a desired state, and the LDH layer 12 may be formed on the surface of the conductive substrate 11 in a desired state. As a result, the electrode 1 for water electrolysis is likely to have high durability. The promotion of mixing of the solution may be achieved while the container containing the solution and the conductive substrate 11 is sealed, or may be achieved under an inert gas atmosphere. 4Ni 2+ Cl - 2+ 2Fe 3+ Cl - 3+ 2Ni→5Ni 2+ Cl - 2+ 2Fe 2+ Cl - 2+ 1Ni Equation (2)
[0047] In the production of the water electrolysis electrode 1, the molar ratio of the Fe ion content to the Ni content in the conductive base material 11 is not limited to a specific value. The molar ratio is, for example, 0.75 or less. In this case, it is possible to prevent the nickel in the conductive base material 11 from dissolving due to the reaction shown in formula (2), which would make it difficult to produce the water electrolysis electrode 1.
[0048] The molar ratio is preferably from 0.05 to 0.25. In this case, the LDH layer 12 is more likely to be formed uniformly on the surface of the conductive substrate 11, and a water electrolysis electrode 1 having high electrode activity is more likely to be produced.
[0049] In the manufacture of the water electrolysis electrode 1, the value obtained by dividing the molar content of Fe ions by the surface area of the conductive base material 11 is not limited to a specific value. The value is, for example, 0.29 mmol / cm 2 In this case, it is possible to prevent the nickel contained in the conductive base material 11 from dissolving due to the reaction shown in formula (2), which would make it difficult to manufacture the water electrolysis electrode 1.
[0050] In the manufacture of the water electrolysis electrode 1, the molar content of Fe ions divided by the surface area of the conductive substrate 11 is preferably 0.01 mmol / cm 2 to 0.1 mmol / cm 2 In this case, the LDH layer 12 is more likely to be formed uniformly on the surface of the conductive substrate 11, and a water electrolysis electrode 1 having high electrode activity is more likely to be produced.
[0051] The chelating agent contained in the solution may be selected with reference to the above examples of the chelating agent contained in the LDH layer 12. The chelating agent contained in the solution preferably contains at least one selected from the group consisting of acetylacetone and citrate. This increases the stability of the dispersion of the complex in the solution, and makes it easier for the LDH layer 12 to be formed in a desired state in the water electrolysis electrode 1. As a result, the water electrolysis electrode 1 is more likely to have high electrode activity.
[0052] FIG. 3 is a schematic diagram showing the mechanism of manufacturing the water electrolysis electrode according to the first embodiment. As shown in FIG. 3, the conductive substrate 11 is immersed in a solution containing transition metal ions TM1, transition metal ions TM2, and a chelating agent 30. For example, the transition metal ions TM1 are nickel ions, and the transition metal ions TM2 are iron ions. In addition, nickel is present on the surface of the conductive substrate 11. A part of the transition metal ions TM2 etches and dissolves nickel present on the surface of the conductive substrate 11. A part of the chelating agent 30 reacts with the surface of the conductive substrate 11 to form a complex C1 between the transition metal ions TM1 and the chelating agent 30 derived from the conductive substrate 11. In addition, when the solution is adjusted to be alkaline, a complex C1 derived from the transition metal ions TM1 and the chelating agent 30 derived from the solution is formed in the solution, and a complex C2 between the transition metal ions TM2 and the chelating agent 30 is formed. Next, the complexes C1 and C2 react on the surface of the conductive substrate 11 to synthesize LDH 20 along the surface of the conductive substrate 11. In addition, the complexes C1 and C2 contain the chelating agent 30, which inhibits crystal growth of the LDH 20. As a result, an LDH layer 12 containing the LDH 20 and the chelating agent 30 is formed on the surface of the conductive substrate 11, and an electrode 1 for water electrolysis is obtained.
[0053] The water electrolysis electrode 1 according to the present embodiment can be used, for example, as an electrode of a water electrolysis cell of an alkaline water electrolysis apparatus or an anion exchange membrane type water electrolysis apparatus. The water electrolysis electrode 1 is used, for example, in at least one selected from the group consisting of an anode and a cathode in these water electrolysis apparatuses. This tends to increase the activity of the anode reaction or cathode reaction in water electrolysis.
[0054] Second embodiment Fig. 4 is a cross-sectional view illustrating an example of a water electrolysis cell according to the second embodiment. As illustrated in Fig. 4, the water electrolysis cell 2 includes an anode 2a, a cathode 2b, and a diaphragm 2p. At least one selected from the group consisting of the anode 2a and the cathode 2b includes, for example, the water electrolysis electrode 1 according to the first embodiment. In this case, the activity of the anode reaction or the cathode reaction in the water electrolysis cell 2 is likely to be high, and the anode 2a or the cathode 2b is likely to exhibit high performance.
[0055] The water electrolysis cell 2 is, for example, an alkaline water electrolysis cell that uses an alkaline aqueous solution. The alkaline aqueous solution used in the water electrolysis cell 2 is not limited to a specific alkaline aqueous solution. Examples of the alkaline aqueous solution include an aqueous potassium hydroxide solution and an aqueous sodium hydroxide solution.
[0056] 4, the water electrolysis cell 2 includes, for example, an electrolytic cell 2s, a first chamber 2m, and a second chamber 2n. The diaphragm 2p is disposed inside the electrolytic cell 2s and separates the inside of the electrolytic cell 2s into the first chamber 2m and the second chamber 2n. The anode 2a is disposed in the first chamber 2m, and the cathode 2b is disposed in the second chamber 2n.
[0057] The diaphragm 2p is, for example, a diaphragm for alkaline water electrolysis. The diaphragm 2p is, for example, a sheet-like porous membrane. The diaphragm 2p has a thickness of, for example, 100 μm to 500 μm and has holes that serve as passages for ions or an electrolyte. The material of the diaphragm 2p is not limited to a specific material. Examples of the material of the diaphragm 2p are asbestos, polymer-reinforced asbestos, potassium titanate bound with polytetrafluoroethylene (PTFE), zirconia bound with PTFE, and antimonic acid and antimony oxide bound with polysulfone. Other examples of the material of the diaphragm 2p are sintered nickel, nickel coated with ceramics and nickel oxide, and polysulfone. The diaphragm 2p may be Zirfon Perl UTP 500 manufactured by AGFA.
[0058] The anode 2a may be disposed in a zero-gap state in which it is in contact with the diaphragm 2p, or may be disposed with a gap between it and the diaphragm 2p. The cathode 2b may be disposed in a contact state with the diaphragm 2p, or may be disposed with a gap between it and the diaphragm 2p.
[0059] The water electrolysis cell 2 electrolyzes an alkaline aqueous solution to produce hydrogen and oxygen. An aqueous solution containing a hydroxide of an alkaline metal or an alkaline earth metal is supplied to the first chamber 2m. In addition, an alkaline aqueous solution can be supplied to the second chamber 2n. Electrolysis is performed while an alkaline aqueous solution of a predetermined concentration is discharged from the first chamber 2m and the second chamber 2n, and hydrogen and oxygen are produced.
[0060] When the anode 2a includes the water electrolysis electrode 1, the cathode 2b may include, for example, an electrode material known as a cathode for an alkaline water electrolysis cell.
[0061] In the water electrolysis cell 2, when the cathode 2b includes the water electrolysis electrode 1, the anode 2a may include a known electrode material for the anode of an alkaline water electrolysis cell. In the water electrolysis cell 2, both the anode 2a and the cathode 2b may include the water electrolysis electrode 1.
[0062] According to the above configuration, at least one selected from the group consisting of the anode 2a and the cathode 2b includes the water electrolysis electrode 1, so that the water electrolysis cell 2 can exhibit high performance.
[0063] Third embodiment Fig. 5 is a cross-sectional view illustrating an example of a water electrolysis apparatus according to the third embodiment. As illustrated in Fig. 5, the water electrolysis apparatus 3 includes the water electrolysis cell 2 according to the second embodiment and a voltage applicator 40. The voltage applicator 40 applies a voltage between the cathode 2b and the anode 2a. The water electrolysis apparatus 3 is an alkaline water electrolysis apparatus that uses an alkaline aqueous solution.
[0064] The voltage applicator 40 is electrically connected to the anode 2a and the cathode 2b. The voltage applicator 40 makes the potential of the anode 2a higher than the potential of the cathode 2b. The voltage applicator 40 is not limited to a specific type of voltage applicator as long as it can apply a voltage between the anode 2a and the cathode 2b. The voltage applicator 40 may be a device that adjusts the voltage applied between the anode 2a and the cathode 2b. When the voltage applicator 40 is connected to a DC power source such as a battery, a solar cell, or a fuel cell, the voltage applicator 40 includes, for example, a DC / DC converter. When the voltage applicator 40 is connected to an AC power source such as a commercial power source, the voltage applicator 40 includes, for example, an AC / DC converter. The voltage applicator 40 may be, for example, a power-type power source. In the power-type power source, the voltage applied between the anode 2a and the cathode 2b and the current flowing between the anode 2a and the cathode 2b are adjusted so that the power supplied to the water electrolysis device 3 becomes a predetermined set value.
[0065] With the above configuration, the water electrolysis device 3 can exhibit high performance.
[0066] (Fourth embodiment) Fig. 6 is a cross-sectional view illustrating an example of a water electrolysis cell according to the fourth embodiment. As illustrated in Fig. 6, the water electrolysis cell 4 includes an anode 4a, a cathode 4b, and an anion exchange membrane 4p. In the water electrolysis cell 4, at least one selected from the group consisting of the anode 4a and the cathode 4b includes, for example, the water electrolysis electrode 1 according to the first embodiment. In this case, the activity of the anode reaction or the cathode reaction in the water electrolysis cell 4 is likely to be high, and the anode 4a or the cathode 4b is likely to exhibit high performance.
[0067] The water electrolysis cell is, for example, an anion exchange membrane (AEM) type water electrolysis cell. As shown in Fig. 6, the anode 4a includes, for example, a catalyst layer 4m and a gas diffusion layer 4n. The cathode 3b includes, for example, a catalyst layer 4j and a gas diffusion layer 4k. The catalyst layer 4m of the anode 4a is in contact with one main surface of the anion exchange membrane 4p, and the catalyst layer 4j of the cathode 4b is in contact with the other main surface of the anion exchange membrane 4p.
[0068] The anion exchange membrane 4p is not limited to a specific type of anion exchange membrane. The anion exchange membrane 4p has conductivity of anions such as hydroxide ions. The anion exchange membrane 4p can prevent the oxygen gas generated at the anode 4a from mixing with the hydrogen gas generated at the cathode 4b. The oxygen gas passes through the gas diffusion layer 4n and is led to the outside of the anode 4a. The hydrogen gas passes through the gas diffusion layer 4k and is led to the outside of the cathode 4b.
[0069] In the water electrolysis cell 4, when the anode 4a includes the water electrolysis electrode 1, the cathode 4b may be a known cathode for AEM-type water electrolysis cells. In this case, the LDH layer 12 of the water electrolysis electrode 1 can function as the catalyst layer 4m, and the conductive substrate 11 of the water electrolysis electrode 1 can function as the gas diffusion layer 4n.
[0070] In the water electrolysis cell 4, when the cathode 4b includes the water electrolysis electrode 1, the anode 4a may be a known anode for an AEM-type water electrolysis cell. In this case, the LDH layer 12 of the water electrolysis electrode 1 can function as the catalyst layer 4j, and the conductive substrate 11 of the water electrolysis electrode 1 can function as the gas diffusion layer k. In the water electrolysis cell 4, both the anode 4a and the cathode 4b can include the water electrolysis electrode 1.
[0071] According to the above configuration, at least one selected from the group consisting of the anode 4a and the cathode 4b includes the water electrolysis electrode 1, so that the water electrolysis cell 4 can exhibit high performance.
[0072] Fifth embodiment Fig. 7 is a cross-sectional view illustrating an example of a water electrolysis apparatus according to a fifth embodiment. As illustrated in Fig. 7, the water electrolysis apparatus 5 includes a water electrolysis cell 4 and a voltage applicator 40. The voltage applicator 40 applies a voltage between the cathode 4b and the anode 4a. The water electrolysis apparatus 5 is, for example, an AEM type water electrolysis apparatus.
[0073] The voltage applicator 40 is electrically connected to the anode 4a and the cathode 4b. The voltage applicator 40 makes the potential of the anode 4a higher than the potential of the cathode 4b. The voltage applicator 40 is not limited to a specific type of voltage applicator as long as it can apply a voltage between the anode 4a and the cathode 4b. The voltage applicator 40 may be a device that adjusts the voltage applied between the anode 4a and the cathode 4b. When the voltage applicator 40 is connected to a DC power source such as a battery, a solar cell, or a fuel cell, the voltage applicator 40 includes, for example, a DC / DC converter. When the voltage applicator 40 is connected to an AC power source such as a commercial power source, the voltage applicator 40 includes, for example, an AC / DC converter. The voltage applicator 40 may be, for example, a power-type power source. In the power-type power source, the voltage applied between the anode 4a and the cathode 4b and the current flowing between the anode 4a and the cathode 4b are adjusted so that the power supplied to the water electrolysis device 5 becomes a predetermined set value.
[0074] With the above configuration, the water electrolysis device 5 can exhibit high performance.
[0075] (Additional Note) From the above description, the following techniques are disclosed. (Technology 1) A sheet-like conductive substrate; a layered double hydroxide layer containing two or more types of transition metals provided on a surface of the conductive substrate; The layered double hydroxide layer contains a chelating agent. Electrode for water electrolysis. (Technology 2) The two or more transition metals include at least two selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Cu, W, and Ru; The electrode for water electrolysis according to claim 1. (Technology 3) The two or more transition metals include at least one selected from the group consisting of Ni and Fe. The water electrolysis electrode according to claim 2. (Technology 4) The chelating agent includes at least one selected from the group consisting of acetylacetone and citrate. The electrode for water electrolysis according to any one of claims 1 to 3. (Technology 5) The layered double hydroxide layer has a thickness of 35 nm or more. 5. An electrode for water electrolysis according to any one of claims 1 to 4. (Technology 6) The surface of the conductive substrate is made of nickel. 6. An electrode for water electrolysis according to any one of claims 1 to 5. (Technology 7) The nickel has a purity of 90% by mass or more. The water electrolysis electrode according to claim 6. (Technology 8) 8. The electrode for water electrolysis according to claim 1, wherein the conductive substrate has a porous structure. (Technology 9) An anode; A cathode; a diaphragm; At least one selected from the group consisting of the anode and the cathode comprises the water electrolysis electrode according to any one of techniques 1 to 8. water electrolysis cell. (Technology 10) An anode; A cathode; an anion exchange membrane, At least one selected from the group consisting of the anode and the cathode comprises the water electrolysis electrode according to any one of techniques 1 to 8. water electrolysis cell. (Technology 11) The water electrolysis cell according to claim 9 or 10, A voltage applicator that applies a voltage between the cathode and the anode. Water electrolysis equipment. (Technology 12) The method includes immersing a sheet-shaped conductive substrate in a solution containing a chelating agent and two or more types of transition metal ions, and adjusting the solution to an alkaline state. A method for manufacturing an electrode for water electrolysis. (Technology 13) increasing the pH of the solution. A method for producing an electrode for water electrolysis according to claim 12. (Technology 14) The two or more transition metal ions include ions of at least two transition metals selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Cu, W, and Ru; 14. A method for producing an electrode for water electrolysis according to claim 12 or 13. (Technology 15) The two or more transition metal ions include an ion of at least one transition metal selected from the group consisting of Ni and Fe. A method for producing an electrode for water electrolysis according to claim 14. (Technology 16) The surface of the conductive substrate is made of nickel. 16. A method for producing an electrode for water electrolysis according to any one of claims 12 to 15. (Technology 17) The conductive substrate comprises nickel, The two or more transition metal ions include an Fe ion, the solution comprises chloride ions; Promoting mixing of the solution before adjusting the solution to be alkaline while the conductive substrate is immersed. 17. A method for producing an electrode for water electrolysis according to claim 15 or 16. (Technology 18) The molar ratio of the Fe ion content to the Ni content contained in the conductive base material is 0.75 or less. A method for producing an electrode for water electrolysis according to claim 17. (Technology 19) The molar ratio of the Fe ion content to the Ni content contained in the conductive base material is 0.05 to 0.25. A method for producing an electrode for water electrolysis according to claim 17. (Technology 20) The molar content of Fe ions divided by the surface area of the conductive substrate is 0.29 mmol / cm 2 Below is the A method for producing an electrode for water electrolysis according to claim 17. (Technology 21) The molar content of Fe ions divided by the surface area of the conductive substrate is 0.01 mmol / cm 2 to 0.1 mmol / cm 2 That is, A method for producing an electrode for water electrolysis according to claim 17. (Technology 22) The chelating agent includes at least one selected from the group consisting of acetylacetone and citrate. 22. A method for producing an electrode for water electrolysis according to claim 12. EXAMPLES
[0076] The present disclosure will be described in more detail below with reference to examples. Note that the following examples are merely examples of the present disclosure, and the present disclosure is not limited to the following examples.
[0077] Example 1 A mixed solvent was prepared by mixing 6.688 milliliters (mL) of water and 10.032 mL of ethanol. Ethanol was purchased from Fujifilm Wako Pure Chemical Industries, Ltd. In the mixed solvent, the volume of water:volume of ethanol was 2:3. A solution was prepared by dissolving 0.5685 g of nickel chloride hexahydrate and 0.3233 g of iron chloride hexahydrate in the mixed solvent. Nickel chloride hexahydrate and iron chloride hexahydrate were purchased from Fujifilm Wako Pure Chemical Industries, Ltd. 0.113 mL of acetylacetone (ACAC) was added to this solution as a chelating agent to obtain a chelating agent-containing solution. ACAC was purchased from Sigma-Aldrich. The substance amount of ACAC in the chelating agent-containing solution was 1 / 3.25 of the total substance amount of Ni ions and Fe ions. The chelating agent-containing solution was acidic.
[0078] Five Ni meshes manufactured by Nilaco were washed with acetone for 10 minutes and with a 1M HCl aqueous solution for 10 minutes to degrease the Ni meshes and remove impurities. The wire diameter of the Ni meshes was 0.1 mm, the number of meshes was 60, and each Ni mesh was circular with a diameter of 15 mm in plan view. The total weight of the five Ni meshes was 0.281 g. Next, the Ni meshes were washed with water and dried to complete the cleaning process of the Ni meshes.
[0079] Next, the Ni mesh after the cleaning process was immersed in the above-mentioned chelating agent-containing solution. In this state, the chelating agent-containing solution containing the Ni mesh was shaken and stirred at 25°C for 24 hours. At this time, the outermost surface of the Ni mesh was etched according to the above-mentioned formula (2). In this case, the molar ratio of the Fe ion content to the Ni content contained in the Ni mesh was 0.25. In addition, the value obtained by dividing the molar content of Fe ions by the surface area of the Ni mesh was 0.0942 millimoles (mmol) / cm. 2 The surface area of the Ni mesh was determined by considering the wire size, mesh number, and the geometric shape of the Ni mesh based on the diameter.
[0080] Next, 1.216 mL of propylene oxide (POX) was added to the chelating agent-containing solution as a pH-increasing agent. The amount of POX added was adjusted so that the ratio of the amount of POX to the amount of chloride ions in the mixed solution was 2. The resulting mixed solution was shaken and stirred at 25°C for 72 hours. During the shaking and stirring of the mixed solution, it was understood that POX gradually captured hydrogen ions in the mixed solution, and the pH of the mixed solution gradually increased and became alkaline. After shaking and stirring for 72 hours, the Ni mesh was collected, washed with water and dried. In this way, the electrode according to Example 1 was obtained.
[0081] Example 2 An electrode according to Example 2 was prepared in the same manner as in Example 1, except for the following points. The Ni mesh after the cleaning process was placed in the chelating agent-containing solution, and immediately thereafter, POX was added to the chelating agent-containing solution. In other words, in Example 2, the chelating agent-containing solution containing the Ni mesh was not shaken or stirred before the addition of POX.
[0082] Example 3 An electrode according to Example 3 was prepared in the same manner as in Example 1, except for the following points. 0.535 mL of water and 0.803 mL of ethanol were mixed in the preparation of the mixed solvent. In the mixed solvent, the volume of water:volume of ethanol was 2:3. The amount of nickel chloride hexahydrate dissolved in the mixed solvent was 0.0455 g, and the amount of iron chloride hexahydrate dissolved in the mixed solvent was 0.0259 g. The amount of ACAC added in the preparation of the chelating agent-containing solution was 0.009 mL, and the substance amount of ACAC in the chelating agent-containing solution was 1 / 3.25 of the total substance amount of Ni ions and Fe ions. Two Ni meshes were used, and the total mass of the two Ni meshes was 0.112 g. The molar ratio of the content of Fe ions to Ni contained in the Ni mesh in the shaking and stirring of the chelating agent-containing solution containing the Ni mesh was 0.05. In addition, the value obtained by dividing the molar content of Fe ions by the surface area of the Ni mesh was 0.0188 mmol / cm 2 It was.
[0083] Example 4 An electrode according to Example 4 was prepared in the same manner as in Example 1, except for the following points. In the preparation of the mixed solvent, 6.900 mL of water and 10.351 mL of ethanol were mixed. In the mixed solvent, the volume of water:volume of ethanol=2:3. The amount of nickel chloride hexahydrate dissolved in the mixed solvent was 5.8654 g, and the amount of iron chloride hexahydrate dissolved in the mixed solvent was 3.3351 g. In the preparation of the chelating agent-containing solution, the amount of ACAC added was 1.164 mL, and the substance amount of ACAC in the chelating agent-containing solution was 1 / 3.25 of the total substance amount of Ni ions and Fe ions. Four Ni meshes were used, and the total mass of the four Ni meshes was 0.96 g. Each Ni mesh was a square with a side length of 20 mm in a plan view. The amount of POX added to the chelating agent-containing solution was 12.545 mL. The molar ratio of the Fe ion content to the Ni content in the Ni mesh in the chelating agent-containing solution containing the Ni mesh when it was shaken was 0.75. In addition, the molar content of Fe ions divided by the surface area of the Ni mesh was 0.2844 mmol / cm 2 The amount of POX added was adjusted so that the ratio of the amount of POX to the amount of chloride ions in the mixed solution of the chelating agent-containing solution and POX was 2.
[0084] Example 5 An electrode according to Example 5 was prepared in the same manner as in Example 1, except for the following points. The amount of nickel chloride hexahydrate dissolved in water was 0.336 g, and the amount of iron chloride hexahydrate was 0.191 g. The amount of ACAC added in the preparation of the chelating agent-containing solution was 0.033 mL, and the substance amount of ACAC in the chelating agent-containing solution was 1 / 3.25 of the total substance amount of Ni ions and Fe ions. Instead of a Ni mesh, one Ni plate was used, and its mass was 0.335 g. The Ni plate had a circular shape with a diameter of 15 mm in a plan view. The amount of POX added to the chelating agent-containing solution was 3.63 mL. The molar ratio of the content of Fe ions to Ni contained in the Ni plate in the shaking and stirring of the chelating agent-containing solution containing the Ni plate was 0.04. In addition, the value obtained by dividing the molar content of Fe ions by the surface area of the Ni plate was 0.073 mmol / cm 2 The amount of POX added was adjusted so that the ratio of the amount of POX to the amount of chloride ions in the mixed solution of the chelating agent-containing solution and POX was 2.
[0085] Comparative Example 1 A mixed solvent was prepared by mixing 6.900 mL of water and 10.351 mL of ethanol. Ethanol was purchased from Fujifilm Wako Pure Chemical Industries, Ltd. In the mixed solvent, the volume of water:volume of ethanol was 2:3. A solution was prepared by dissolving 5.8654 g of nickel chloride hexahydrate and 3.3351 g of iron chloride hexahydrate in the mixed solvent. Nickel chloride hexahydrate and iron chloride hexahydrate were purchased from Fujifilm Wako Pure Chemical Industries, Ltd. 1.164 mL of acetylacetone (ACAC) was added to this solution as a chelating agent to obtain a chelating agent-containing solution. ACAC was purchased from Sigma-Aldrich. The substance amount of ACAC in the chelating agent-containing solution was 1 / 3.25 of the total substance amount of Ni ions and Fe ions. The pH of the chelating agent-containing solution was 1.
[0086] A Ni mesh manufactured by Nilaco was washed with acetone for 10 minutes and with a 1M HCl aqueous solution for 10 minutes to degrease the Ni mesh and remove impurities. The Ni mesh had a wire diameter of 0.1 mm, 60 meshes, and was a square with a side length of 20 mm in plan view. The Ni mesh weighed 0.25 g. The Ni mesh was then washed with water and dried to complete the cleaning process of the Ni mesh.
[0087] Next, the Ni mesh after the cleaning process was immersed in the above-mentioned chelating agent-containing solution. In this state, the chelating agent-containing solution containing the Ni mesh was shaken and stirred at 25°C for 24 hours. At this time, the entire Ni mesh was etched and dissolved according to the above-mentioned formula (2). For this reason, in Comparative Example 1, an electrode that could be evaluated was not obtained. The molar ratio of the Fe ion content to the Ni content contained in the Ni mesh was 2.9. In addition, the value obtained by dividing the molar content of Fe ions by the surface area of the Ni mesh was 1.0919 mmol / cm 2 It was.
[0088] Comparative Example 2 An electrode according to Comparative Example 2 was produced in the same manner as in Example 1, except that ACAC was not used.
[0089] Comparative Example 3 Five Ni meshes that had been subjected to a cleaning treatment in the same manner as in Example 1 were used as electrodes according to Comparative Example 3.
[0090] [Identification of electrode structure and morphological observation] A sample for morphological observation was picked up and processed using a focused ion beam processing and observation device (FIB) FB-2200 manufactured by Hitachi High-Technologies Corporation. Next, the sample for morphological observation was sliced using a FIB NX5000 manufactured by Hitachi High-Tech Science Corporation to obtain a sample for morphological observation. The structure of the electrode according to each example and each comparative example was identified and the morphology of the electrode was observed by cross-sectional observation using a transmission electron microscope (TEM) JEM-F200 manufactured by JEOL Ltd. and electron beam diffraction using the TEM. In this way, the state of LDH in the electrodes according to the examples and comparative examples was evaluated.
[0091] FIG. 8 is a TEM image of the electrode according to Example 1. FIG. 9A is a TEM image showing a portion of the electrode according to Example 1 where an electron beam diffraction result was obtained. FIG. 9B is an electron beam diffraction image obtained by TEM for the portion of the electrode shown in FIG. 9A. As shown in FIG. 8, it can be seen that a predetermined layer is formed on the surface of the Ni mesh. This layer had a thickness of 35 nm or more. As shown in FIGS. 9A and 9B, according to the electron beam diffraction of this layer, lattice spacings of 0.14 nm, 0.19 nm, and 0.22 nm derived from the LDH lattice were observed, and diffraction interference fringes corresponding to (113), (015), and (012) of LDH, respectively, were confirmed. Therefore, it was confirmed that a layer containing LDH was formed on the surface of the Ni mesh.
[0092] FIG. 10 is a TEM image of the electrode according to Example 2. FIG. 11A is a TEM image showing a portion of the electrode according to Example 2 where the electron beam diffraction results were obtained. FIG. 11B is an electron beam diffraction image obtained by TEM for the portion of the electrode shown in FIG. 11A. FIG. 11B shows the result of electron beam diffraction obtained for the region shown by the white dashed line in FIG. 11A. As shown in FIG. 10, it is understood that LDH exists on a part of the surface of the Ni mesh in the electrode according to Example 2. Also, in FIG. 10, it is confirmed that there are many gaps in the LDH layer. As shown in FIG. 11A and FIG. 11B, lattice-derived spacings of 0.14 nm, 0.17 nm, 0.19 nm, and 0.22 nm due to the LDH lattice were observed, and diffraction interference fringes corresponding to (113), (110), (015), and (012) of LDH, respectively, were confirmed. It was confirmed that LDH exists on the surface of the Ni mesh.
[0093] FIG. 12 is a TEM image of the electrode according to Comparative Example 2. FIG. 13A is a TEM image showing a portion of the electrode according to Comparative Example 2 where the electron beam diffraction results were obtained. FIG. 13B is an electron beam diffraction image obtained by TEM for the portion of the electrode shown in FIG. 13A. FIG. 13B shows the result of electron beam diffraction obtained for the region shown by the white dashed line in FIG. 13A. As shown in FIG. 12, it is understood that LDH exists on a part of the surface of the Ni mesh in the electrode according to Comparative Example 2. As shown in FIG. 13A and FIG. 13B, the lattice-derived interplanar spacings of 0.14 nm, 0.17 nm, 0.19 nm, and 0.22 nm of LDH were observed, and diffraction interference fringes corresponding to (113), (110), (015), and (012) of LDH, respectively, were confirmed. It was confirmed that LDH exists on the surface of the Ni mesh. It is understood that LDH is formed on the surface of the Ni mesh even under the condition of no addition of a chelating agent. It is confirmed that a large number of voids exist in the layer containing LDH in FIG. 12.
[0094] [Evaluation by Fourier transform infrared spectroscopy (FT-IR)] In order to evaluate whether ACAC exists in the sample obtained from the electrode according to Example 5, a Fourier transform infrared spectrum chart of the electrode according to Example 5 was obtained using a Continuum FT-IR device manufactured by Thermo Fisher Scientific under the condition of 32 accumulations, as shown in FIG. 20. As a result, the sample obtained from the electrode according to Example 5 had a wave number of 1581 cm -1 and 1353 cm -1 As shown in FIG. 3(a) of the following reference, the molecule chelated with ACAC has an absorption peak at approximately 1575 cm in the Fourier transform infrared spectroscopy (FT-IR) spectrum. -1 and 1380cm -1 Therefore, this peak is an absorption peak derived from ACAC coordinated to Fe and Ni. From the above results of Example 5, it is presumed that the electrodes according to Examples 1 to 4, which were prepared by adding ACAC, also contain ACAC in the electrodes. Apuchu R. Sangtam et al. “Synthesis and characterization of Co(II)-Co(III) LDH and Ac@Co(II)-Co(III) LDH nanohybrid and study of its application as bactericidal agents”, Results in Chemistry 2022, 4, 100671.
[0095] [Electrode evaluation] The oxygen evolution (OER) overvoltage of the electrodes according to each Example and Comparative Examples 2 and 3 was evaluated. For the measurement, a potentiostat VersaSTAT4 manufactured by Princeton Applied Research, an alkali sample vial (200 mL) manufactured by BAS, a Teflon (registered trademark) cap (for 200 mL) manufactured by BAS, and a plate electrode AE-2 manufactured by EC Frontier were used as a jig for the working electrode. The electrodes according to each Example and Comparative Examples 2 and 3, which are the working electrodes, were fixed to this jig. A double platinum wire counter electrode D.6.0305.200J manufactured by Metrohm was used as the counter electrode. The current derived from the anode reaction of the water electrolysis cell was measured by the three-electrode method under the following measurement conditions. The anode reaction is an oxygen evolution reaction. (Measurement conditions) Solution: 1M KOH solution Onset potential against reversible hydrogen electrode (RHE): 1.0V Turn-around potential for the reversible hydrogen electrode (RHE): 1.55V to 1.7V Number of cycles: 5 cycles Potential sweep speed: 10mV / sec Temperature: 25℃
[0096] Current density at 5th cycle: 10mA / cm 2 The OER overpotential was determined by subtracting the theoretical potential of 1.229 V required to cause the oxygen evolution reaction to proceed from the voltage corresponding to the potential. The results are shown in Table 1. Table 1 also shows the molar ratio of the Fe ion content to the Ni content contained in the Ni substrate, which is the Ni mesh or Ni plate, used in the preparation of the electrode, and the value obtained by dividing the molar content of Fe ions by the surface area of the Ni substrate. Table 1 also shows whether the chelating agent-containing solution containing the Ni substrate was shaken or stirred before the addition of POX, and whether the electrode could be prepared.
[0097] From the measurement results for evaluating the OER overpotential, the coverage of the LDH-containing layer on the surface of the Ni substrate was determined based on the following formula (3). The results are shown in Table 1. In formula (3), S NiOx is the integral of the current density from 1.38 V to 1.48 V, and S Niis the integral value of the current density at a potential from 1.35 V to 1.38 V. The current density peak at a potential from 1.38 V to 1.48 V is a peak derived from nickel and iron hydroxides, and the current density peak at a potential from 1.35 V to 1.38 V is a peak derived from pure nickel. Coverage rate = S NiOx / (S Ni + S NiOx )×100 Equation (3)
[0098] 14 to 18 are graphs showing the measurement results of the OER overpotential of the electrodes according to Examples 1 to 5. In these graphs, the horizontal axis indicates potential, and the vertical axis indicates current density. In a sweep involving reduction from 1.4 V to 1.3 V, the electrodes according to Examples 1, 3, and 5 showed Ni 3+ From Ni 2+ A peak associated with the reduction reaction to is observed. On the other hand, such a peak is hardly observed in the electrodes according to Examples 2 and 4. This indicates that in the electrodes according to Examples 2 and 4, the portion of the layer containing LDH capable of functioning as an electrode is extremely small. For example, in the case of Example 2, as shown in FIG. 10, many gaps exist in the LDH on the surface of the Ni base material, and it is understood that effective LDH electrically connected to the Ni base material is unlikely to exist.
[0099] In the measurement of the OER overpotential, in the electrode according to Example 1, it was not possible to confirm that the LDH-containing layer was desorbed into the KOH solution. On the other hand, in the electrode according to Comparative Example 2, it was confirmed that the surface of the electrode turned black during the measurement of the OER overpotential, and a substance of the same color as the electrode appeared and precipitated in the KOH solution. Therefore, it is considered that in the electrode according to Example 1 containing ACAC, the peeling of the LDH-containing layer from the electrode is suppressed. In the electrode according to Comparative Example 2, it was clearly confirmed that the LDH-containing layer was peeling from the electrode, so it is considered that in the electrode according to Comparative Example 2, the portion of the LDH-containing layer that effectively contributes to the electrode performance is small.
[0100] Comparing Example 4 with Comparative Example 1, it was found that when the molar ratio of the Fe ion content to the Ni content contained in the Ni base material is large, the chemical reaction that dissolves Ni becomes intense, the entire Ni base material dissolves, and an electrode cannot be produced. For this reason, it is understood that the molar ratio of the Fe ion content to the Ni content contained in the Ni base material is preferably 0.75 or less. In addition, the value obtained by dividing the molar content of Fe ions by the surface area of the Ni base material was 0.29 mmol / cm. 2 It is understood that it is desirable that:
[0101] As shown in Table 1, the OER overpotentials of the electrodes according to Examples 1 and 3 are particularly low. Therefore, it was suggested that, from the viewpoint of electrode activity, the molar ratio of the Fe ion content to the Ni content contained in the Ni base material is more preferably in the range of 0.05 to 0.25. In addition, the value obtained by dividing the molar content of Fe ions by the surface area of the Ni base material is 0.01 mmol / cm 2 to 0.1 mmol / cm 2 It was suggested that it would be more desirable to
[0102] [Electrode durability evaluation] The OER overpotential of the electrodes according to Examples 1 and 2 and Comparative Examples 2 and 3 was measured for 1000 cycles to evaluate the durability of the electrodes. For the measurement, a potentiostat VersaSTAT4 manufactured by Princeton Applied Research, an alkali sample vial (200 mL) manufactured by BAS, a Teflon (registered trademark) cap (for 200 mL) manufactured by BAS, and a plate electrode AE-2 manufactured by EC Frontier were used as a jig for the working electrode. The electrodes according to Examples 1 and 2 and Comparative Examples 2 and 3, which are the working electrodes, were fixed to this jig. A double platinum wire counter electrode D.6.0305.200J manufactured by Metrohm was used as the counter electrode. The current derived from the anode reaction of the water electrolysis cell was measured by the three-electrode method under the following measurement conditions. The anode reaction is an oxygen evolution reaction. (Measurement conditions) Solution: 1M KOH solution Potential vs. RHE: 1.0V to 1.7V Maximum number of cycles: 1000 cycles Potential sweep speed: 100mV / sec Temperature: 25℃
[0103] 19 is a graph showing the relationship between the OER overpotential and the number of cycles for the electrodes according to Examples 1 and 2 and the electrodes according to Comparative Examples 2 and 3. In this graph, the OER overpotential is shown for every 50 cycles. Each cycle simulates the start and stop of water electrolysis.
[0104] Comparing Example 1 and Example 2, the OER overpotential does not increase by the 50th cycle in the electrode according to Example 1. On the other hand, the OER overpotential increases by the 50th cycle in the electrode according to Example 2. For this reason, from the viewpoint of the durability of the electrode, it is advantageous to promote mixing of the solution before adjusting the alkalinity of the solution while the Ni base material is immersed in the chelating agent-containing solution, such as by shaking and stirring the chelating agent-containing solution containing the Ni base material.
[0105] According to Comparative Example 3, the OER overpotential increases from the initial stage, and it is understood that the LDH formed on the surface of the Ni base material can play a role in suppressing the deterioration of the electrode.
[0106] However, from the above description, many improvements and other embodiments of the present disclosure will be apparent to those skilled in the art. Therefore, the above description should be interpreted as merely illustrative and is provided for the purpose of teaching those skilled in the art the best mode for carrying out the present disclosure. Substantially alterations in operating conditions, composition, structure and / or function can be made without departing from the spirit of the present disclosure.
[0107] [Table 1] [Industrial Applicability]
[0108] The water electrolysis electrode of the present disclosure can be used as an anode or a cathode in water electrolysis.
Claims
1. A sheet-like conductive substrate; a layered double hydroxide layer containing two or more types of transition metals provided on a surface of the conductive substrate, The layered double hydroxide layer contains a chelating agent. Electrode for water electrolysis.
2. The two or more transition metals include at least two selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Cu, W, and Ru; The electrode for water electrolysis according to claim 1 .
3. The two or more transition metals include at least one selected from the group consisting of Ni and Fe. The electrode for water electrolysis according to claim 2.
4. The chelating agent includes at least one selected from the group consisting of acetylacetone and citrate. The electrode for water electrolysis according to claim 1 .
5. The layered double hydroxide layer has a thickness of 35 nm or more. The electrode for water electrolysis according to claim 1 .
6. The surface of the conductive substrate is made of nickel. The electrode for water electrolysis according to claim 1 .
7. The nickel has a purity of 90% by mass or more. The electrode for water electrolysis according to claim 6.
8. The electrode for water electrolysis according to claim 1 , wherein the conductive substrate has a porous structure.
9. An anode; A cathode; a diaphragm; At least one selected from the group consisting of the anode and the cathode comprises the water electrolysis electrode according to any one of claims 1 to 8. water electrolysis cell.
10. An anode; A cathode; an anion exchange membrane, At least one selected from the group consisting of the anode and the cathode comprises the water electrolysis electrode according to any one of claims 1 to 8. water electrolysis cell.
11. The water electrolysis cell according to claim 9 ; A voltage applicator that applies a voltage between the cathode and the anode. Water electrolysis equipment.
12. A water electrolysis cell according to claim 10, A voltage applicator that applies a voltage between the cathode and the anode. Water electrolysis equipment.
13. the step of immersing a sheet-like conductive substrate in a solution containing a chelating agent and two or more types of transition metal ions and adjusting the solution to an alkaline state to obtain a water electrolysis electrode comprising a layered double hydroxide layer containing two or more types of transition metals and the chelating agent provided on a surface of the conductive substrate; A method for manufacturing an electrode for water electrolysis.
14. increasing the pH of the solution. The method for producing the water electrolysis electrode according to claim 13.
15. The two or more transition metal ions include ions of at least two transition metals selected from the group consisting of V, Cr, Mn, Fe, Co, Ni, Cu, W, and Ru; The method for producing the water electrolysis electrode according to claim 13.
16. The two or more transition metal ions include an ion of at least one transition metal selected from the group consisting of Ni and Fe. The method for producing the water electrolysis electrode according to claim 15.
17. The surface of the conductive substrate is made of nickel. The method for producing the water electrolysis electrode according to claim 13.
18. The conductive substrate comprises nickel, The two or more transition metal ions include Fe ions, the solution comprises chloride ions; Promoting mixing of the solution before adjusting the solution to be alkaline while the conductive substrate is immersed. The method for producing the water electrolysis electrode according to claim 16.
19. The molar ratio of the content of Fe ions to the content of Ni contained in the conductive base material is 0.75 or less. The method for producing the water electrolysis electrode according to claim 18.
20. The molar ratio of the content of Fe ions to the content of Ni contained in the conductive base material is 0.05 to 0.
25. The method for producing the water electrolysis electrode according to claim 18.
21. The molar content of Fe ions divided by the surface area of the conductive substrate is 0.29 mmol / cm 2 Below is the The method for producing the water electrolysis electrode according to claim 18.
22. The molar content of Fe ions divided by the surface area of the conductive substrate is 0.01 mmol / cm 2 to 0.1 mmol / cm 2 That is, The method for producing the water electrolysis electrode according to claim 18.
23. The chelating agent includes at least one selected from the group consisting of acetylacetone and citrate. The method for producing the water electrolysis electrode according to claim 13.
Citation Information
Patent Citations
Preparation method of Mg-doped NiFe-based (oxygen) hydroxide and oxygen evolution electro-catalysis application of Mg-doped NiFe-based (oxygen) hydroxide
CN114959791A
Electrode base, negative electrode for aqueous solution electrolysis using the same, and method for producing the electrode base
JP2011190534A
Alkaline water electrolysis method and anode for alkaline water electrolysis
JP2021139027A
Electrocatalyst for water electrolysis and preparing method of the same
US20220259748A1
Universal One-Step Method to Make Fe-Based (Oxy)Hydroxides as Efficient OER Catalysts for Seawater Electrolysis
US20230010138A1
Cited By
JPWO2024262446A1